Takhrij and Syarah Hadith of Agrotechnology: Ingredients and Benefits of Olive Oil - RA. Astiana Rizky Shahilah; Wahyudin Darmalaksana; Yati Setiati Rachmawati (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with respect to olive oil. This research method is a kind of inheritance of qualitative studies and field studies with approach Takhrij and commentary tradition. The result and discussion of this research is that olive is a special tree and full of blessings and olive oil has various benefits and is highly recommended according to the hadith. The conclusion of this research is that the takhrij and syarah of the Prophet's hadith regarding olive oil with agrotechnical analysis have the opportunity to be developed transdisciplinary.